Inclusive J / ψ production at midrapidity in pp collisions at √s=13 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akbar, Z.; Akindinov, A.; et al. (Springer Science and Business Media Deutschland GmbH, 2021)
We report on the inclusive J/ψ production cross section measured at the CERN Large Hadron Collider in proton–proton collisions at a center-of-mass energy √s = 13 TeV. The J/ψ mesons are reconstructed in the e⁺e⁻ decay channel and the measurements are performed at midrapidity (|y| < 0.9) in the transverse-momentum interval 0 < Pᴛ < 40 GeV/c, using a minimum-bias data sample corresponding to an integrated luminosity Lint = 32.2 nb⁻¹ and an Electromagnetic Calorimeter triggered data sample with Lint = 8.3 pb⁻¹. The Pᴛ-integrated J/ψ production cross section at midrapidity, computed using the minimumbias data sample, is dσ/dy|y₌₀ = 8.97 ± 0.24 (stat) ± 0.48 (syst) ± 0.15 (lumi) μb. An approximate logarithmic dependence with the collision energy is suggested by these results and available world data, in agreement with model predictions. The integrated and Pᴛ-differential measurements are compared with measurements in pp collisions at lower energies and with several recent phenomenological calculations based on the non-relativistic QCD and Color Evaporation models.
Keywords: Physics; Production (economics); Particle physics; Large Hadron Collider; Luminosity; Energy (signal processing); Quantum chromodynamics; Meson; Hadron; Nuclear physics; https://purl.org/pe-repo/ocde/ford#1.03.00